PENANGANAN EROSI LERENG GALIAN DAN TIMBUNAN JALAN DENGAN RUMPUT VETIVER - G. Gunawan; Nanny Kusminingrum (Direktorat Bina Teknik Jalan dan Jembatan, 2008)
Erosion is really a problem in slope areas where the length andinclination of slope influence surface flow and erosion. Double increase of flow in speed leads to the increase of eroding granular soil up to thirty-two fold. When the length of slope is two-fold, the erosion will be 1.5 times. Research result in Indonesia indicated that the degree of erosion in deforested lands reached 120-400 tonnes/ha/year. Such case will obviously give negative impact on road drainage system. Therefore, erosion control technology in roadside slopes should be developed. The purpose of the research is to find out the influence of slope inclination and vegetation on the degree of erosion at the inclination either above or under 60â—¦. Furthermore, erosion control technology is also discussed. To achieved the purpose, the research was done and laboratory prototype of erosion control with vegetation was made. Field research of erosion control technology using vetiver grass combined with bahia grass was carried out. Research showed that the degree of plant lushness and the lushness of slope cover, by covering > 70% of slope, eroding land is almost zero. Planting of vetiver will effectively reduce the degree of erosion when it is planted in lines and bahia grass is planted in between. Key word : control soil erosion, vegetasi, vetiver grass